Political Racism Brexit and its Aftermath - Shaw, Martin (Agenda Publishing Limited, 2022)
Political Racism conceptualizes a distinctive form of racism - intentional, organized hostility mobilized by political actors - and examines its role in the Brexit conflict and in the rise of a new nationalist politics in the UK. In a compelling analysis the book argues that Powellite anti-immigrant racism, reinterpreted in numerical terms, was combined with anti-East European and anti-Muslim hostility to inform the Vote Leave victory. This type of racism, which has a special significance in societies where racism has been delegitimized, is shown to have further shaped the form of EU withdrawal and also the government's post-Brexit policies.